1999
DOI: 10.1053/euhj.1998.1189
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death in the working population; a collaborative study in Central Japan

Abstract: Aim Few epidemiological data are available describing the sudden death of persons in their prime. This study aims to elucidate when and how sudden death occurs among employees.Methods A total of 196 775 employees from 10 workplaces in Central Japan were surveyed for non-traumatic sudden death during 1989-1995. Demographic data and information regarding onset were collected by their workplace healthcare professionals. ResultsWe identified 251 male and 13 female cases of sudden death. The annual incidence was 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…35,36 Regarding cardiovascular and cerebrovascular sudden death, it has been reported that in Japanese working population it occurred more frequently in April, when the new business year starts, compared to other months. 37 It was hypothesized that younger people in Japan might have to face greater occupational stress at the end of the old financial year and the beginning of the new year coinciding with winter and spring. 10,37 The quality of our registration system was assured by its completeness.…”
Section: Chowdhury Turin Et Al Stroke Incidence and Season 749mentioning
confidence: 99%
“…35,36 Regarding cardiovascular and cerebrovascular sudden death, it has been reported that in Japanese working population it occurred more frequently in April, when the new business year starts, compared to other months. 37 It was hypothesized that younger people in Japan might have to face greater occupational stress at the end of the old financial year and the beginning of the new year coinciding with winter and spring. 10,37 The quality of our registration system was assured by its completeness.…”
Section: Chowdhury Turin Et Al Stroke Incidence and Season 749mentioning
confidence: 99%
“…No other study has reported a daily variation of survival, although that of sudden death is well documented. 8,9 Thus, this enigma is still unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of cases are in the middle age group (Table 3, 4,5,6). A smoking habit provided a significantly high correlation for sudden death of all causes and coronary artery disease, so smoking provokes sudden death and abnormal cholesterol concentrations led to rupture of vulnerable plaque.…”
Section: Underlying Causes Of Sudden Deathmentioning
confidence: 99%
“…4 Sudden death has accounted for 50 to 80% of all coronary deaths. 4 Sudden cardiac deaths are accounted for >60% of all sudden deaths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation